BILANGAN DOMINASI LOKASI PADA LINE PAN GRAPH DAN MIDDLE PAN GRAPH - Fransiskus Fran; Elishabet Yohana; Yundari Yundari (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2021)
Let G is a simple, connected, and undirected graph. A set D is a subset of V. If every node of V adjacent to at least one node D, then D is a dominating set of the graph G . One of the topics from dominating set is locating dominating set. Locating dominating set is dominating set on condition if every two vertices u,v elements of V-D satisfy the intersection of N(v) and D not equal to the intersection of N(u) and D with u not equal to v. The locating domination number of a graph G is the minimum cardinality of a locating dominating set in a graph G . In this study discussed the locating domination number on line pan graph (L(Tn,1)) and middle pan graph (M(Tn,1)). Locating domination number was obtained by finding dominating set from some graph. Then, does the dominating set meet the condition of locating dominating set? If it meets locating dominating set condition, then we can find the locating domination number of the graphs. In the last procedure, we get pattern location domination number of line pan graph and middle pan graph. The results of the study obtained the locating domination number of (L(Tn,1)) and (M(Tn,1)) consecutive are floor function of (2n/5)+1 and floor function of ((2n+1)/3)+1.